Gabriel García Márquez entre a ficção e a reportagem - Rockenbach, Fábio Luis (2014)
Journalism and literature have always been subject to discussions between theorists , professionals and researchers , without being able to establish a common denominator about the nature of their relationship . Among the most accepted characteristics that can be identified as regulatory aspects of the difference between the two areas is the fact journalism is based on a belief in the truth, and literature permit the use of fiction. From these basic definitions, this study aims to understand how principles of journalism and literary possibilities arise harmoniously throughout the production of Colombian writer Gabriel Garcia Marquez, renowned both for its fictional production as the work in different journalistic publications. The work turns to the study of journalism of his early days as a reporter and later investigates the use of techniques of journalistic text and production routines of journalism in the narrative of Chronicle of a Death Foretold. The corpus was chosen because it was defined by the author as a false report and, simultaneously, a fake romance . This is a study of bibliographic nature, which also examines the importance of journalism in the formation of the writer adressed and their acceptance or rejection to standards of journalistic text. Necessary for understanding the relationships that are established between careers as a journalist and literary career of the author cited, this study makes use of the works of authors who study the convergences and departures between the two areas, as well as the journalistic work of Gabriel García Márquez